Moderasi Beragama dalam Pandangan Hukum Islam dan Aplikasinya Dalam Pendidikan - Dafril; Syafrianto; Rusydi; Riki Saputra; Sri Wahyuni (Journal of Social, Educational and Religious Studies, 2026)
Religious moderation is a fundamental principle in Islam that emphasizes balance (tawazun), justice (i'tidal), tolerance (tasamuh), and the middle path (tawassuth) in religious life. This article aims to analyze the concept of religious moderation from the perspective of Islamic law and examine its implications for Islamic education. This study employed a qualitative approach using a library research method by reviewing primary and secondary sources, including the Qur’an, Hadith, classical and contemporary Islamic legal literature, academic journals, and official documents related to religious moderation. Data were analyzed using content analysis to identify key concepts, principles, and educational implications of religious moderation. The findings reveal that religious moderation is an integral part of Islamic law, reflected in the objectives of Sharia (maqashid al-shari'ah), the principles of justice, tolerance, consultation, equality, and legal flexibility. In the context of Islamic education, religious moderation can be implemented through curriculum development, inclusive learning approaches, and the creation of a tolerant and dialogical educational environment. However, religious moderation has clear normative boundaries and does not imply compromising core Islamic beliefs, including the principles of tawhid, Sharia, and Islamic morality. Therefore, religious moderation serves as a strategic framework for strengthening social harmony, preventing religious extremism, and fostering an inclusive and peaceful Islamic civilization.